The Plasticity of Dendritic Cell Responses to Pathogens and Their Components - Huang, Qian; Liu, Dongyu; Majewski, Paul; Schulte, Leah C.; Korn, Joshua M.; Young, Richard A.; Lander, Eric S.; Hacohen, Nir (Science (American Association for the Advancement of Science), 2001)
Dendritic cells are involved in the initiation of both innate and adaptive immunity. To systematically explore how dendritic cells modulate the immune system in response to different pathogens, we used oligonucleotide microarrays to measure gene expression profiles of dendritic cells in response to Escherichia coli, Candida albicans, and influenza virus as well as to their molecular components. Both a shared core response and pathogen-specific programs of gene expression were observed upon exposure to each of these pathogens. These results reveal that dendritic cells sense diverse pathogens and elicit tailored pathogen-specific immune responses.